Estructura, productividad de madera y regeneración natural de Juglans neotropica Diels en la Hacienda la Florencia del cantón y provincia de Loja - Vaca Llivigañay, Jason Alejandro (2022)
In recent years man has drastically altered natural ecosystems, as is the case of Andean ecosystems by anthropic activities such as agriculture, livestock, infrastructure and deforestation, which has caused the species that inhabits these ecosystems as Juglans neotropica Diels (Nogal) to lower its wood productivity and therefore is currently in danger of extinction. That is why, in order to generate information on the structure, productivity and natural regeneration of the species in the wild, this thesis project studied a remnant forest of Juglans neotropica Diels, located in the hacienda La Florencia on the hill "El Zañe" belonging to the canton and province of Loja. A forest inventory was used by the statistical method of systematic sampling in an effective area of 14 hectares, recording all individuals with diameters ≥10 cm diameter at breast height (DAP). Data such as tree number, tree location, DAP 1,30 cm, commercial height (HC) and total height (HT) in meters were also measured. Regarding the structure of the species, the Morisita index and the Lamprecht protocol were used. On the other hand, for wood productivity, all registered individuals were classified by diameter classes and in turn in potential and commercial, to know if they comply or not with the minimum cutting diameter (DMC). For the natural regeneration, 4 plots were installed, in which the high grassland, low grassland and saplings were recorded. The results of this study for the Morisita index showed a value of Iδ= 1.26, which means that the species has an aggregate distribution; as for the tree component, it reached a maximum height of 32.40 m and a minimum of 10.32 m. The wood productivity of this forest remnant resulted in 141.17 m³/ha of total volume and 76.22 m³/ha of commercial volume. In addition, 13 individuals were recorded in the low and high latizal categories, while no individuals were recorded in the brinzal category. Based on the results obtained, it can be concluded that the species is in a state of succession with little natural regeneration and therefore currently in danger of extinction. Furthermore, it is advisable to carry out studies that help to understand the dynamics of the natural regeneration of the Species (Ver Anexo 6). Keywords: Juglans neotropica, structure, wood productivity, strata, natural regeneration.